Domestic Violence against Women during COVID-19 Pandemic in Nepal - Dhital, Madhu Koirala; Laudari, Raju; Owens, Vickie; Regmi, Nabin; Dhital, Shalik Ram (Journal of Karnali Academy of Health Sciences, 2023)
Domestic violence perpetrated is a public health problem commonly for women in developing nation like Nepal. Major causes of domestic violence are unemployment, alcohol drink, lack of education, loneliness, crowded living spaces, lack of privacy. These factors may be aggravated by pandemic such as COVID-19. Women experience from domestic violence due to dominant patriarchal culture combined with a lack of self-awareness and education amongst adult males. Domestic violence is mostly instigated by intimate partners and maybe intensified due to the unusual stress of pandemic stress and spending increased time with wives and families. Domestic violence usually manifested in the form of adverse physical, mental and social health. The COVID-19 pandemic may have increased that adverse health of women in Nepal. Preventive strategies of domestic violence could be self-awareness, counselling, create a job, stop living alone at home, sharing with all family members and strong governmental rules. This paper argues the effects of COVID-19 pandemic on domestic violence and possible preventive strategies of domestic violence.